2009
DOI: 10.1002/iub.184
|View full text |Cite
|
Sign up to set email alerts
|

Retinal deimination in aging and disease

Abstract: SummaryDeimination is a posttranslational modification and refers to the conversion of protein bound arginine into citrulline. In the retina, deimination is predominantly catalyzed by Peptidylarginine deiminase type 2 (PAD2). PAD2 expression and deimination are found in many different retinal layers: choroid, retinal pigment epithelium (RPE), photoreceptors, inner plexiform layer, inner nuclear layer, and retinal ganglion cell (RGC) layer. Although decreased retinal deimination and PAD2 expression have been fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
36
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 31 publications
(37 citation statements)
references
References 43 publications
1
36
0
Order By: Relevance
“…Zhao et al (57) and Fuchshofer et al (58) investigated the role of TGF-␤, proposing its importance in the pathogenesis of glaucoma. Bhattacharya et al (53) found a positive link between the presence of PAD2 and glaucoma and in more recent research this group has outlined the occurrence of retinal deiminization (59,60), further confirming the post-translational effects and their role in glaucoma. Tezel and colleagues (14,61,62) have used proteomics to determine the role of oxidative stress on retinal proteins in glaucoma, the influence of hemoglobin expression and regulation, (16) and the importance of the complement pathway (62).…”
mentioning
confidence: 80%
“…Zhao et al (57) and Fuchshofer et al (58) investigated the role of TGF-␤, proposing its importance in the pathogenesis of glaucoma. Bhattacharya et al (53) found a positive link between the presence of PAD2 and glaucoma and in more recent research this group has outlined the occurrence of retinal deiminization (59,60), further confirming the post-translational effects and their role in glaucoma. Tezel and colleagues (14,61,62) have used proteomics to determine the role of oxidative stress on retinal proteins in glaucoma, the influence of hemoglobin expression and regulation, (16) and the importance of the complement pathway (62).…”
mentioning
confidence: 80%
“…One of the main reasons is that the upregulation of PAD4 has been especially found in rheumatoid arthritis (RA) patients, which is believed to play causative role in the onset and progression of RA [6][7][8][9]. Besides, aberrant increase of PAD 4 has also been involved in multiple sclerosis, glaucoma and even cancers [10][11][12]. Therefore, with the deciphering the relation between PAD4 and different disease models [13,14], PAD4 has emerged as a potential therapeutic target for human diseases.…”
Section: Introductionmentioning
confidence: 97%
“…In our prior studies, we found that PAD2 expression and deimination, in response to pressure, is decreased in RGCs (M. EnriquezAlgeciras and D. Ding, unpublished observations) in contrast with an increase in astrocytes (34,36). This opposite deimination pattern in astrocytes and RGCs was conjectured earlier (15). Insults such as hydrostatic pressure, hypoxia, and chemokines on an isolated mixed population of cells derived from CD1 mouse brain show similar increase and decrease in deimination in the astrocytes and neurons (data not shown).…”
Section: Discussionmentioning
confidence: 59%
“…In the retina, the hyperdeiminated regions are less pronounced than in the brain and are likely contributed by retinal epithelial cells or other glial cells. A change in the deimination is also expected to alter protein-protein interactions and, as a consequence, functional biological pathways (15). It is important to note that no known enzyme exists for reversal of deimination, rendering it a long-term modification to be reversed by protein turnover.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation